Las Casas y sus fieles repetidores - Javier Molina Villeta (Mélanges de la Casa de Velázquez, 2024)
This article addresses a double historical and historiographical problem that concerns two key figures in the history of the conquest of America: the Dominican from Seville, Bartolomé de las Casas, and the historian from Soria, Francisco López de Gómara, whom Las Casas accused of being a “servant” who wrote “falsehoods” at the behest his master, Hernán Cortés. This statement had great significance in later historiography and is still repeated by most authors, despite the fact that it has been shown to be unfounded. We propose to examine in detail the context of this infamy and the causes and consequences it provoked. Through the analysis of archival and historiographical sources, we will try to elucidate to what extent the Dominican’s attack could have affected the prohibition of Gómara’s work. We will also reflect on the reasons why later historians repeated the defamation of Las Casas.